PTEN‐PI3K pathway alterations in advanced prostate cancer and clinical implications - Choudhury, Atish D. (The Prostate, 2022)
Background Despite significant advances in molecular characterization and therapeutic targeting of advanced prostate cancer, it remains the second most common cause of cancer death in men in the United States. The PI3K (Phosphatidylinositol 3‐kinase)/AKT (AKT serine/threonine kinase)/mTOR (mammalian target of rapamycin) signaling pathway is commonly altered in prostate cancer, most frequently through loss of the PTEN (Phosphatase and Tensin Homolog) tumor suppressor, and is critical for cancer cell proliferation, migration, and survival. Methods This study summarizes signaling through the PTEN/PI3K pathway, alterations in pathway components commonly seen in advanced prostate cancer, and results of clinical trials of pathway inhibitors reported to date with a focus on more recently reported studies. It also reviews rationale for combination approaches currently under study, including with taxanes, immune checkpoint inhibitors and poly (ADP‐ribose) polymerase inhibitors, and discusses future directions in biomarker testing and therapeutic targeting of this pathway. Results Clinical trials studying pharmacologic inhibitors of PI3K, AKT or mTOR kinases have demonstrated modest activity of specific agents, with several trials of pathway inhibitors currently in progress. A key challenge is the importance of PI3K/AKT/mTOR signaling in noncancerous tissues, leading to predictable but often severe toxicities at therapeutic doses. Results Further advances in selective pharmacologic inhibition of the PI3K/AKT/mTOR pathway in tumors, development of rational combinations, and appropriate biomarker selection to identify the appropriate tumor‐ and patient‐specific vulnerabilities will be required to optimize clinical benefit from therapeutic targeting of this pathway.